Association between hemoglobin-to-red blood cell distribution width ratio and hospital mortality in patients with non-traumatic subarachnoid hemorrhage - Liu, Jiuling; Wang, Junhong (Frontiers in Neurology, 2023)
Background In patients with ischemic stroke, low hemoglobin-to-red blood cell distribution width ratio (HRR) was associated with an increased risk of mortality. However, it was unknown in the non-traumatic subarachnoid hemorrhage (SAH) population. The purpose of this study was to examine the association between baseline HRR and in-hospital mortality in patients with non-traumatic SAH. Methods Non-traumatic SAH patients were screened out of the Medical Information Mart for Intensive IV (MIMIC-IV) database between 2008 and 2019. The Cox proportional hazard regression models were utilized to analyze the association between baseline HRR and in-hospital mortality. Restricted cubic splines (RCS) analysis was utilized to determine the relationship curve between hospital mortality and the HRR level and examine the threshold saturation effect. We further applied Kaplan–Meier survival curve analysis to examine the consistency of these correlations. The interaction test was used to identify subgroups with differences. Results A total of 842 patients were included in this retrospective cohort study. Compared with individuals with lower HRR Q1 ( ≤ 7.85), the adjusted HR values in Q2 (7.86–9.15), Q3 (9.16–10.16), and Q4 (≥10.17) were 0.574 (95% CI: 0.368–0.896, p = 0.015), 0.555 (95% CI: 0.346–0.890, p = 0.016), and 0.625 (95% CI: 0.394–0.991, p = 0.045), respectively. The association between the HRR level and in-hospital mortality exhibited a non-linear relationship (p < 0.05). The threshold inflection point value of 9.50 was calculated using RCS analysis. When the HHR level was lower than 9.50, the risk of in-hospital mortality rate decreased with an adjusted HR of 0.79 (95% CI: 0.70–0.90, p = 0.0003). When the HRR level was higher than 9.50, the risk of in-hospital mortality almost hardly increased with the increase in the HRR level (adjusted HR = 1.18, 95% CI: 0.91–1.53, p = 0.2158). K-M analysis showed that patients with low HRR levels had significantly higher in-hospital mortality (p < 0.001). Conclusion There was a non-linear connection between the baseline HRR level and in-hospital mortality. A low level of HRR could increase the risk of death in participants with non-traumatic SAH.